Profesionalisme Guru PAI dalam Meningkatkan Kualitas Pembelajaran di SMP Negeri 1 Momalia Bolaang Mongondow Selatan - Darmawati Zakaria (Jurnal Ilmiah AL-Jauhari: Jurnal Studi Islam dan Interdisipliner, 2022)
This paper aims to explore the professional achievements of PAI teachers in improving learning at the State Junior High School 1 Momalia. Based on the exposure of data and findings in the field as well as the results of research discussions, it is shown that the improvement of the professionalism of PAI teachers at SMP Negeri 1 Momalia is carried out through four teacher competencies, namely personal competence, pedagogic competence, social competence and professional competence. The four competencies are carried out in synergy, perfecting each other in all teacher activities in schools. However, the competencies possessed by PAI teachers at SMP Negeri 1 Momalia are currently still not at a perfect level, there is still a need for improvement and improvement of these competencies. Because basically teacher competence is always dynamic, developing according to the needs, conditions and demands of education, especially PAI teachers with religious problems that are always evolving.